2014
DOI: 10.12809/hkmj134095
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation primary central nervous system lymphoma in a patient with systemic lupus erythematosus and prolonged use of immunosuppressant

Abstract: Post-transplantation primary central nervous system lymphoma is an uncommon and fatal post-transplant lymphoproliferative disorder. Such lymphomas have been described in only a few case series in the literature. The incidence of this condition is rising with improved survival after organ transplantation. A case of post-transplantation primary central nervous system lymphoma in a young Chinese woman with systemic lupus erythematosus is described here. She presented with right-sided weakness and memory loss afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
3
Order By: Relevance
“…The most significant finding was a lack of responses to first-line therapy which was a poor prognosticator [5]. In 2014, Tse et al report complete resolution of CNS PTLD following treatment with rituximab and whole brain radiation [13]. Current accepted treatment modalities include reduction in immunosuppression, chemotherapy, rituximab, whole brain radiation, and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant finding was a lack of responses to first-line therapy which was a poor prognosticator [5]. In 2014, Tse et al report complete resolution of CNS PTLD following treatment with rituximab and whole brain radiation [13]. Current accepted treatment modalities include reduction in immunosuppression, chemotherapy, rituximab, whole brain radiation, and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…La survenue d'un lymphome du SNC chez un patient lupique reste exceptionnelle puisque seuls 14 cas ont été publiés à ce jour à notre connaissance [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Onze cas sont résumés dans le tableau, un cas n'étant pas renseigné [21], le diagnostic de LED étant incertain dans un second cas [25] et le lymphome étant survenu chez une patiente suivie pour un LES ayant eu une transplantation rénale [26], ce qui peut être un facteur confondant.…”
Section: Discussionunclassified
“…Onze cas sont résumés dans le tableau, un cas n'étant pas renseigné [21], le diagnostic de LED étant incertain dans un second cas [25] et le lymphome étant survenu chez une patiente suivie pour un LES ayant eu une transplantation rénale [26], ce qui peut être un facteur confondant. Il s'agit de femmes d'âge moyen (42,5 ans en médiane), présentant des signes neurologiques focaux, pour lesquelles le diagnostic de lymphome du SNC est évoqué sur l'aspect nodulaire des lésions avec rehaussement périphérique lors de l'injection de produit de contraste à l'imagerie.…”
Section: Discussionunclassified
“…ere are reported cases in the literature with the use of Mycophenolate-Mofetil in various autoimmune diseases with an association of PCNSL, possibly due to Epstein-Barr Virus (EBV) driven B-cell lymphoproliferative disease mechanism. [10][11][12][13] Kaulen et al performed a 15-year retrospective cohort study for these cases and found that the majority (87%) of cases are DLBCL and are largely (78%) EBV positive. [14] e imaging features of PCNSL in immunocompromised patients significantly differ from the above and are characterized by irregular margins, heterogeneity, and ring enhancement.…”
Section: Pcnsl In Immunocompromised Patientsmentioning
confidence: 99%
“…[14] e imaging features of PCNSL in immunocompromised patients significantly differ from the above and are characterized by irregular margins, heterogeneity, and ring enhancement. [6,13] e lesions are typically showing heterogeneous peripheral enhancement with central non-enhancement (due to necrosis) [Figure 5]. [6,13,15] is is in contrast to solid homogeneous enhancement from that of immunocompetent patients.…”
Section: Pcnsl In Immunocompromised Patientsmentioning
confidence: 99%